2020
DOI: 10.1080/2090598x.2020.1749800
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic vs laser lithotripsy for mid-ureteric stones: Clinical and cost effectiveness results of a prospective trial in a developing country

Abstract: Objective To compare the management of large ureteric stones (>10 mm) with ureterorenoscopy (URS) and laser or pneumatic lithotripsy, and their associated costs. Patients and methods Our prospective study followed the tenets of the Declaration of Helsinki and included 101 patients with large mid-ureteric stones eligible for URS and lithotripsy, and was conducted between January 2018 and August 2019. Patients were randomly divided into two groups: Group 1 had laser litho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…11,12 Nour et al study has reported significantly longer time in pneumatic lithotripsy that was due to the need for retrieval of relatively larger stone fragments in comparison to laser where this time is reduced due to combined fragmentationdusting technique. 6 The mean hospital stay was also similar in the pneumatic and laser lithotripsy group which was similar to other studies. 13 Post-operative stenting after surgery is recommended to reduce postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…11,12 Nour et al study has reported significantly longer time in pneumatic lithotripsy that was due to the need for retrieval of relatively larger stone fragments in comparison to laser where this time is reduced due to combined fragmentationdusting technique. 6 The mean hospital stay was also similar in the pneumatic and laser lithotripsy group which was similar to other studies. 13 Post-operative stenting after surgery is recommended to reduce postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results of putting stents in both the groups were also found in other studies. 6 Many researcher have already shown earlier in their studies that post-operative obstruction and other complications can be minimized by using these stents, that was the reason of putting these stents in most the patients in our study and has also been used in other studies. [14][15][16] Stone migration rate in present study was found significantly more in pneumatic group.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations